Problem Based Learning (PBL): Bagaimana penerapannya dalam pembelajaran teknik passing bolavoli? - Prayoga, Muhammad Fahmi (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
This study aims to determine the effect of the problem based learning model on the learning outcomes of volleyball passing technique students of class XI IPA 3 and 4 at SMAN 15 Semarang. The research method used is quantitative research methods with the type of Quasi Experimental research model. The sample of this research was students of class XI IPA 3 and 4 of SMAN 15 Semarang using purposive sampling technique. Methods of data analysis using paired sample-t-test with a significant level of 5%. The results of the research of 20 students of class XI IPA 3 (passing under) and 20 students of class XI IPA 4 (passing over) showed that there was an increase in the learning outcomes of over and under passing through the application of the Problem Based Learning model. Increase in upper passing class by 16%. Increase in Underpass Class by 17%. The conclusion of this research is that there is an increase in the results of learning over and under passing through the Problem Based Learning learning model at SMAN 15 Semarang because in the use of this learning model students are given freedom in learning.